Plant Growth-Promoting Rhizobacteria Alleviate High Salinity Impact on the Halophyte Suaeda fruticosa by Modulating Antioxidant Defense and Soil Biological Activity - Hidri, Rabaa; Mahmoud, Ouissal Metoui-Ben; Zorrig, Walid; Mahmoudi, Henda; Smaoui, Abderrazak; Abdelly, Chedly; Azcon, Rosario; Debez, Ahmed (Frontiers in Plant Science, 2022)
Plant growth-promoting rhizobacteria (PGPR) are considered as bio-ameliorators that confer better salt resistance to host plants while improving soil biological activity. Despite their importance, data about the likely synergisms between of PGPR and halophytes in their native environments are scarce. The objective of this study was to assess the effect of PGPR (Glutamicibacter sp. and Pseudomonas sp.) inoculation on biomass, nutrient uptake, and antioxidant enzymes of Suaeda fruticosa, an obligate halophyte native in salt marshes and arid areas in Tunisia. Besides, activity of rhizospheric soil enzymes activities upon plant inoculation was determined. Plants were grown in pots filled with soil and irrigated with 600 mM NaCl for one month. Inoculation (either with Pseudomonas sp. or Glutamicibacter sp.) resulted in significantly higher shoot dry weight and less accumulation of Na+ and Cl− in shoots of salt-treated plants. Glutamicibacter sp. inoculation significantly reduced malondialdehyde (MDA) concentration, while increasing the activity of antioxidant enzymes (superoxide-dismutase SOD; catalase, CAT; ascorbate peroxidase, APX and glutathione reductase, GR) by up to 100%. This provides strong arguments in favour of a boosting effect of this strain on S. fruticosa challenged with high salinity. Pseudomonas sp. inoculation increased shoot K+ and Ca+ content and lowered shoot MDA concentration. Regarding the soil biological activity, Pseudomonas sp. significantly enhanced the activities of three rhizospheric soil enzymes (urease, ß-glucosidase and dehydrogenase) as compared to their respective non-inoculated control under salinity. Hence, Pseudomonas sp. could have a great potential to be used as bio-inoculants in order to improve plant growth and soil nutrient uptake under salt stress. Indole- 3-acetic acid (IAA) concentration in the soil increased in both bacterial treatments under saline conditions, especially with Glutamicibacter sp. (up to +214%). As a whole, Glutamicibacter sp. and Pseudomonas sp. strains are promising candidates as part of biological solutions aiming at the phytoremediation and reclamation of saline-degraded areas.